PUBLIC GOODS AND SUSTAINABLE TOURISM: THE CONSTRUCTION OF WHITE ELEPHANTS - JUAN GABRIEL BRIDA (ASEAN Journal on Hospitality and Tourism, 2008)
In this paper, following the seminal paper of Robinson and Torvik (2005), we analyze the effects for a sustainable tourism of the construction ofwhite elephants. We present a formal definition and the main characteristics ofwhite elephants. In particular, we introduce this concept in the framework of tourist activities and describe some examples in this economic sector. We show that white elephants are a particular type of investments projects with negative surplus and that it is the very inefficiency that makes them politically attractive. Finally, we analyze the rationality of this kind of investment on the tourism sector showing the existence of a double rationality in the construction of a white elephant: the rationality ofpoliticians that use these investments to obtain electoral benefits and the social rationality based on economic efficiency.